Synthesis and characterization on atomphospheric plasma sprayed amorphous silica doped hydrxoyapatite coatings - Liao, H. L. (2012)
Plasma sprayed hydroxyapatite (HA) coatings have been widely investigated for application on surface of biomedical metals to improve bonding and interaction between body tissues and implant. In this study, a small amount of amorphous silicon dioxide (silica,~1, 2, 5 wt.%) was introduced into HA slurry which was subsequently spray-dried into powder form. The powder feedstock was then sprayed onto Ti6Al4V alloy substrates by an atmospheric plasma spraying technology. To improve the bonding strength of as-sprayed coatings, the substrates were pre-heat treated to 250 °C by plasma. The characteristics of the as sprayed coatings were investigated by various technologies inclusive of scanning electron microscopy (SEM), X-ray diffraction and X-ray photoelectron spectrometry, and Raman spectrometry. The adhesive bonding strength of the as-sprayed coatings was specified using a universal testing system. Modulus and hardness of the coatings were investigated using nano-hardness tester. The results showed that, with pre- substrate heat treatment, the presence silica have enhanced the hardness, modulus and adhesive strength of coatings. Incorporation of Si has affected the structure of HA crystal involving the exchange of oxygen and silicon. In addition, in vitro osteoblasts cellular responses were assessed and discussed to investigate the cell proliferation and differentiation on the as sprayed coatings.